Semiconductor optical amplifiers - Dutta, Niloy K., 1953- (World Scientific Pub., 2006)
This invaluable book provides a comprehensive treatment of the design and applications of the semiconductor optical amplifier (SOA). SOAs are important components for optical communication systems with applications as in-line amplifiers and as functional devices in evolving optical networks. The functional applications of SOAs were first studied in the early 1990s; since then, the diversity and scope of such applications have been steadily growing. "Semiconductor Optical Amplifiers" is self-contained and unified in presentation. The treatments in the book are detailed enough to capture the interest of the curious reader and sufficiently complete to provide the necessary background to explore the subject further. It is intended to be used as an advanced text by graduate students and by practicing engineers but is also suitable for non-experts who wish to have an overview of optical amplifiers.
Keywords: Optical amplifiers.; Optical communications.; elektronické knihy; electronic books